LAW AND LABOUR EFFECTS OF THE DEATH OF AND THE LOSS OF LEGAL CAPACITY OF AN EMPLOYER BEING A NATURAL PERSON - Dragićević, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
A natural person or a legal one may find themself in the role of an employer. In the former case, a natural person as such or a natural person in the capacity of a sole trader or a freelancer appears as the subject of an employment relationship. Since a natural person is identified with their own enterprise in the latter case (they constitute one body), the question arises what happens in the event of a loss or change in the legal status of a natural person themself being the employer (a holder of a sole proprietorship), which will primarily take place in the event of their death or their loss of legal capacity. Since the labour legislation of the Republic of Serbia does not provide an answer to this question, the author is going to seek for the answer to the question within the general rules of labour, inheritance, family and company laws in her paper. In that sense, in the paper, the effects of the death of and the loss of legal capacity of an employer being a natural person upon the existing employment relationships will primarily be analysed; and this by answering the question whether the employer’s death necessarily causes the termination of employment or such employment may be continued by the employer’s successors (in which case, it may be considered as the change of employer). The author will give a particular attention to the provisions of the Law on Business Companies, which address the possibilities to continue conducting the business in the event of the sole trader’s death; while implicating their shortcomings, unclarities and issues that they cause in the interpretation and the practical application thereof.